Respuesta :

Answer:

[-1, -6]

Step-by-step explanation:

Since both coefficients next to your y's are identical use the Elimination Method by multiplying one of the equations by -1 to form additive inverses, meaning they result in 0:

-1[{2x - 3y = 16}]↷

{5x - 3y = 13}

{-2x + 3y = -16

{5x - 3y = 13

----------------

3x = -3 [Divide by 3]

x = -1

y = -6 [plug in "-1" back into both equations to confirm their authenticities]

https://youtu.be/zcC7wsn3b2g

Watch the above You-Tube link and subscribe for more information on how to solve a system of equations in two to three variables [USERNAME: MATHEMATICS WIZARD].

I am joyous to assist you anytime.